SMEs, Age, and Jobs : A Review of the Literature, Metrics, and Evidence - Aga, Gemechu; Francis, David C.; Rodriguez Meza, Jorge (World Bank, Washington, DC, 2015)
The subject of which firms are the key employers—and which of these create or destroy jobs at a faster rate—is eminently important for academics and policy makers. The relative importance of small versus large firms and old versus young firms has in particular been extensively debated and studied. Nevertheless, the results often hinge on the questions that are asked. Moreover, the categorical definitions used to define firm size and age, and the nature and coverage of the data used have important effects. This paper lays out the relevant definitions and metrics that are central to the debate, reviewing the main findings to date on the subject (with particular emphasis on results in developing economies). The paper adds updated results for 117 developing economies using the World Bank’s Enterprise Survey Data, finding that (i) small and medium enterprises and older establishments are the dominant employers in the nonagricultural private sector labor force in developing economies, and (ii) net job creation is negatively correlated with establishment age and, although the effect of size is also negative, its significance is sensitive to the definition and methods used.